The Organization Of Dual Teaching Within The Sy - Akbota SeitovaUlzharkyn Аbdigapbarova, Elvira Yeshenkulova,; Gulnar Mussabekova, Znanyl Madalieva, Turgyn Baidauletova, (Opción, 2019)
The aim of research is to reveal the features of contemporary higher pedagogical education within the context of the studied theme via the analysis of philosophical, psychological, pedagogical, sociological, normative documents connected with the research problem. As a result, pedagogical conditions of the organization of dual teaching in the course of professional training of future primary school teachers are developed and implemented. In conclusion, the organization of dual teaching in the system of professional education will be productive if pedagogical conditions of dual teaching of future primary school teachers are theoretically proved, developed and realized.